Exploring affinity receptors in bioanalysis: from natural binders to biomimetics - F. Vivaldi; F. Torrini; F. Spiaggia; F. Di Francesco; M. Minunni (Sensors and Actuators Reports, 2025)
Affinity receptors have played a pivotal role in advancing bioanalysis, primarily for diagnostic and therapeutic purposes, thanks to their high selectivity toward target molecules, which enables their use in complex biofluids. While antibodies remain the gold standard, ongoing research has explored alternative receptors with improved stability, reduced size, and enhanced performance in bioanalytical and clinical applications. This works traces the evolution of affinity receptors from classical antibodies to emerging biomimetic and synthetic alternatives, including affibodies, nanobodies, aptamers, and molecularly imprinted polymers (MIPs). We highlight their molecular features, advantages, and limitations, emphasizing their use as part of the molecular toolbox for bioanalytical assay development and biosensing. Overall, the continuous diversification of affinity binders reflects the dynamic nature of this field, where the optimal receptor remains context dependent. For this reason, the research into new binders to complement or eventually replace antibodies that, for the moment, remain the choice for high-throughput applications, is still ongoing.